2014
DOI: 10.1371/journal.pone.0108019
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Barriers to Exercise in Adults with Type 1 Diabetes (T1DM) and How Best to Address Them: A Qualitative Study

Abstract: BackgroundRegular physical activity has recognised health benefits for people with T1DM. However a significant proportion of them do not undertake the recommended levels of activity. Whilst questionnaire-based studies have examined barriers to exercise in people with T1DM, a formal qualitative analysis of these barriers has not been undertaken. Our aims were to explore attitudes, barriers and facilitators to exercise in patients with T1DM.MethodologyA purposeful sample of long standing T1DM patients were invit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
116
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 24 publications
6
116
1
4
Order By: Relevance
“…Lack of time and work schedules for adults and parents are also barriers [53, 59]. Thus, clinical recommendations for exercise may need to incorporate specific strategies to mitigate the risk of hypoglycemia associated with changes in activity level.…”
Section: Physical Activity and Individuals With T1dmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of time and work schedules for adults and parents are also barriers [53, 59]. Thus, clinical recommendations for exercise may need to incorporate specific strategies to mitigate the risk of hypoglycemia associated with changes in activity level.…”
Section: Physical Activity and Individuals With T1dmentioning
confidence: 99%
“…Thus, clinical recommendations for exercise may need to incorporate specific strategies to mitigate the risk of hypoglycemia associated with changes in activity level. Other barriers to physical activity for adults include lack of motivation, embarrassment about weight, lack of access to a gym, frustration with exercise-induced hypoglycemia [59], and lack of social support to engage in physical activity [52, 53]. …”
Section: Physical Activity and Individuals With T1dmentioning
confidence: 99%
“…Certain types of activity may be limited due to the perception of a greater risk of hypoglycemia and difficulty managing it (Lascar et al, 2014). Many struggle to adhere to the recommended guidelines due to anxiety, FOH, and habituated responses to FOH (Lawton et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to exercise in T1D are also common. In a very interesting article, Lascar et al 15 identified the following barriers: inadequate access to facilities, embarrassment regarding body image, and diabetes-specific barriers such as insufficient knowledge about how to manage diabetes before, during, and after exercise. 9.…”
mentioning
confidence: 99%